Effectiveness of Adjunctive Reboxetine on Deficit Symptoms of Schizophrenia - Shafti , Saeed Shoja (International Journal of Psychosocial Rehabilitation, 2014)
Objective: Deficit syndrome is an important dilemma against social participation of schizophrenic patients. Reboxetine is a norepinephrine reuptake inhibitor (NRI) .Objective of this study was to evaluate its effect on the negative symptoms of schizophrenia. Method: in a 12-week randomized placebo-controlled trial, reboxetine was compared with placebo, as an ad- junctive to haloperidol (5 mg), for treatment of 50 patients meeting DSM-IV-TR criteria for schizophrenia. In this respect, Scale for Assessment of Negative Symptoms (SANS) was used as the primary outcome measure. Treatment efficacy was analyzed by t test, Split-plot (Mixed) and repeated –measures analysis of variance (ANOVA). Result: The primary finding of this trial was a significant reduction in mean total scores of SANS in the re- boxetine group, in comparison with the placebo group, at the end of the 12th week (P <0.0001). As well, in the experiment group, all of the sub-scales of SANS demonstrated considerable improvement. A trivial escalation in mean total scores of SAPS also was evident in the later group. Effect Size (ES) analysis too at the end of the trial, pointed to a large improvement with reboxetine. Conclusion: reboxetine, as adjuvant to haloperidol, may cause a favorable outcome on behalf of improvement of deficit symptoms of schizophrenia.